FORM AND FUNCTION OF PENDHAPA (TRADITIONAL JAVANESE HALL) IN JAVANESE SOCIETY - Tri Prasetyo Utomo; Bani Sudardi; Wakit Abdullah; Nanang Rizali Sardjono, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Pendhapa in this paper is a traditional Javanese hall. The form and function of Pendhapa have a characteristic. The discussion of Pendhapa in this paper is more emphasis on form and function in building communication in the Javanese people. It shows the form and functions of the pendhapa. The method of this research is qualitative research. We use observation, in-depth interviews, and content analysis. The research found that pendhapa generally shaped Joglo, and is the only house that is owned by noble persons. Joglo is in the square a with four-poster as the main pillar. The four pillars support the roof towering in the middle. The main pillar in the Joglo house is often called Saka Guru. And the roof in the middle of the Joglo house is called the roof Brunjung. Pendhapa initially serves as a gathering place and deliberation. Pendhapa is the place of social interaction between citizens to know each other. In traditional Javanese houses, Pendhapa is often called a front home and serves as a living room. Pendhapa is often also called an open room or public room. However, in its development Pendhapa can function as a social communication space or can also be called social communication media. It is associated with the development of the culture and lifestyle of the people in the open society.